Multiplier decomposition within Regional SAMs: the case of Andalusia - M. Carmen Lima Díaz; M. Alejandro Cardenete Flores (European Regional Science Association (ERSA), 2004)
In this work we present a methodology of multipliers decomposition (including an employment multiplier), for a regional economy as Andalusia using Social Accounting Matrices (SAM). These matrices are able to enlarge the information provided by the input-output analysis, because they complete the interindustrial flows of an economy with the behaviour of productive factors, consumers, public sector and foreign sector. This database allows us to capture conclusions about intersectoral dependences in a region in a double sense: firstly, from a partial perspective based on the results derived for every year, and secondly from an structural point of view along the decade of the nineties. Keywords: social accounting matrix, regional accounting, structural analysis. JEL classification: C67, D57, R15.
Keywords: C67; D57; R15; 330; social accounting matrix; regional accounting; structural analysis